ASSISTIVE AND EDUCATIONAL TECHNOLOGIES FOR CHILDREN WITH AUTISM SPECTRUM DISORDER: A BIBLIOMETRIC STUDY - Daniele Mesquita Batista; Emilly Vasconcelos Goulart; Ana Ricelly Pereira de Oliveira; Pâmela Farias Santos; Rubenilson Caldas Valois; Maria Goreth Silva Ferreira (Universidade Federal do Paraná, 2024)
Objective: To map the scientific production and create a bibliographic portfolio on developing educational and assistive technologies for children with autism spectrum disorder. Method: Bibliometric study and application of the Methodi Ordinatio for creating a bibliographic portfolio. Articles were searched in databases from 2004 to 2023. The VOSViewer Software and JabRef were used for the bibliometric analysis, and the RanKIn spreadsheet was used for the calculation of the InOrdinatio.  Results: 120 references were found, of which 81 were included in the bibliometric analysis and 56 in the Methodi Ordinatio. The largest number of publications occurred in 2022 (15%), and the article with the highest InOrdinatio was published in 2019. The journal Journal of Autism and Developmental Disorders stood out. The most used terms were Autistic Disorder, Child, Child Development Disorders Pervasive, Only Child, and Autism Spectrum Disorder. Conclusion: More national research is needed to enhance the capabilities of autistic children.